THE ROLE OF SHARIA MANAGEMENT IN THE DEVELOPMENT OF PRODUCTS AND SERVICES IN ISLAMIC BANKING IN INDONESIA - Agus Wahyu Irawan (PAPUA: International Journal of Sharia Business Management, 2024)
The growth of Islamic banking in Indonesia faces challenges in product and service development due to limited management expertise in Sharia compliance. Despite the increasing demand for Sharia-compliant financial products, the industry's ability to innovate and expand its offerings is hindered by a lack of specialized knowledge and skills among managers. This research investigates the role of Sharia management in enhancing the quality and variety of Islamic banking offerings. The study aims to address the gap between market demands and current Sharia banking products, identifying key factors that contribute to or hinder the development process. Utilizing a qualitative research method, data were collected through interviews with key stakeholders in the Islamic banking sector and analysis of relevant documents. The interviews provided insights into the experiences and perspectives of industry professionals, while the document analysis offered a broader understanding of regulatory and operational contexts. The results indicate that effective Sharia management significantly improves product innovation and service quality. Managers with a deep understanding of Sharia principles can better navigate the complexities of developing compliant products, leading to more robust and diverse offerings. Furthermore, strong adherence to Sharia principles builds customer trust and loyalty, as clients feel more confident in the ethical and religious integrity of the services provided. The research also reveals that ongoing training and development for Sharia managers are crucial for sustaining growth. As the market evolves, continuous education ensures that managers remain adept at applying Sharia principles in innovative ways. Finally, the findings suggest that collaboration between Islamic banking institutions and regulatory bodies can enhance the overall efficiency of Sharia management practices. By working together, these entities can create a more supportive environment for product development, ensuring that Islamic banking in Indonesia continues to grow and meet the needs of its customers.